The relationship of management modality in Saudi patients with type 2 diabetes to components of metabolic syndrome, γ glutamyl transferase and highly sensitive C-reactive protein. (September 2016) - Bahijri, Suhad M.; Ahmed, Maimoona; Al-Shali, Khalid; Bokhari, Samia; Alhozali, Amani; Borai, Anwar; Gusti, Amani; Ajabnoor, Ghada; Alghamdi, Ahmed; Asiri, Mohammed; Tuomilehto, Jaakko
Background: The aim of this study was to investigate the relationship among management modality, glycemic control, components of metabolic syndrome (MS) and serum levels of γ glutamyl transferase (GGT) and C-reactive protein (CRP) in patients with type 2 diabetes (T2DM). Methods: Patients with T2DM, not suffering from diabetes complications, were recruited from outpatients clinics at two hospitals in Jeddah. Anthropometric measurements and blood pressure (BP) were taken. A treatment plan was recorded. Fasting blood samples were obtained to measure glucose, glycated hemoglobin (HbA1c), lipids profile, highly sensitive (hs)-CRP and GGT. Results: A total of 71 men and 82 women were recruited. Lower mean HbA1c was found in people receiving oral glucose-lowering drugs compared with those on insulin therapy ( p < 0.001). Management modality had no effect on mean GGT or hs-CRP. Higher mean GGT was associated with poor glycemic control, dyslipidemia, hypertension, and abdominal obesity. GGT correlated significantly ( p < 0.05) and directly with triglycerides in men ( r = 0.401) and diastolic BP ( r = 0.279 for men, r = 0.194, for women), but inversely with high-density lipoprotein cholesterol (HDL-C) ( r = −0.298 for men, r = −0.171 for women). hs-CRP correlated with waist circumference ( p < 0.05, r = 0.312, for men, r = 0.305, for women), with a higher mean being found in men with poor glycemic control ( p = 0.015), in hypertensive women ( p = 0.030), and in patients who were abdominally obese ( p < 0.05). Conclusions: High levels of GGT and hs-CRP are associated with components of MS and poor glycemic control, hence increased cardiovascular risk. Due to their value as independent risk predictors of vascular injury, these measures should be included in routine monitoring of patients with T2DM.